Music Criticism on Moniuszko: Sources and Attitudes - Ciesielski, Rafał (Interdisciplinary Studies in Musicology, 2025)
The aim of this article is to present the conditions and issues which, as recurring themes, essentially determined the content and criteria of Moniuszko debates in Polish music criticism, and shaped the scope and formula of commentary on the composer and his work from the first statements (1839) to the beginning of the 21st century. The arrangement of these issues took into account, on the one hand, the historical and social situation in which Moniuszko operated and, on the other, issues universal to art. These issues included, in particular, the aesthetic attitude and profile of Moniuszko’s work under the partitions, the Polish nature of his music, the way it was received and functioned in the public consciousness, the relationship between Moniuszko and Chopin, and the propaganda dimension of the composer’s work. The permanence of these issues and the questions posed about Moniuszko’s attitude and work were constantly confronted with changing political, social and aesthetic-musical conditions, which fundamentally determined the nature of the answers given to these questions. In the absence of fundamental research into Moniuszko’s work, this meant that the image of Moniuszko in music criticism and, at the same time, in the collective consciousness remained, on the one hand, a function of the changing conditions in which the relevant opinions were formulated and, on the other, was often based on a superficial, ad hoc and non-artistic view. This arrangement was characterised by the relevance of general relationships in Moniuszko’s reception space: universal – national, artistic – utilitarian, current – timeless, etc., which, it seems, created an adequate space for reflection on the phenomenon of Moniuszko. Perhaps this configuration of space was, in the case of the composer (is it always so?), the source of the creation of his myth in the collective consciousness.